Evidencia empírica de los factores que afectan a la independencia del auditor - Fernández Rodriguez, Maria (2013)
The European Union considers it appropriate to further discuss how to strengthen the independence of the auditors to address conflicts of interest inherent in the current scenario, characterized by factors such as the appointment of auditors for the audited company, low turnover or different service delivery to the audit. This paper aims to realize the expectations of the factors that affect, both positively and negatively, the auditor maintains its independence from the client.